(untitled) (Research, Society and Development, 2022)
This study sought to assess the effects that the SARS-CoV-2, pandemic had on the pediatric population of Brazilian regions, with regard to dental care. This is a descriptive study that used as a source, secondary data of a quantitative nature, acquired on the websites of (IBGE) and SIA/SUS, the Ministry of Health’s information bank (DATASUS) in the period of six months before and in the that starts and continues the Covid-19 pandemic. In the period that begins the pandemic by SARS-CoV-2, the Southeast and North regions were, respectively, in first and last place in the age group from 5 to 9 years old, with regard to non-invasive procedures, this same age group added the highest number in invasive techniques. The study confirmed that in the period of the pandemic, the search for procedures considered invasive has decreased notably. It is concluded that the Covid-19 pandemic has reduced the demand for dental care in the public network, for invasive procedures, with this, it is expected that there will be an increase in care after the end of the pandemic, due to possible repressed demand, which was obtained during the pandemic period, while for non-invasive procedures there was no decrease in the number of procedures performed.